2008
DOI: 10.1017/s0954394508000045
|View full text |Cite
|
Sign up to set email alerts
|

Sociolinguistic patterns in grammaticalization:He, they, andthosein human indefinite reference

Abstract: A B S T R A C T Sociolinguistic patterns in language change are largely based on generalizations from linguistic variables consisting of lexemes or morphemes. This article takes a diachronic, corpus-based approach to the diffusion of a change in a more extensive morphosemantic function consisting of several linguistic subsystems. It focuses on the pronoun variants he, they, and those used for human indefiniteness in two contexts: (a) epicene anaphoric uses with indefinite pronouns and (b) cataphoric personal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Like the source noun, though, it seems to have retained the sense of ‘male’: with only two exceptions the man pronouns in all four sources of data were uttered by male speakers (the two exceptions were extracted from Anuvahood , uttered by the same female speaker and addressed on each occasion to her boyfriend). Laitinen's () analysis of the development of he, they and those as indeterminate pronouns in Early and Late Modern English found that women strongly disfavoured the use of masculine he as an indeterminate pronoun, presumably, he suggests, because they were avoiding a form that for them indexed masculine gender. Similar gendered patterns are found in studies focussing on the loss of – man in indefinite pronouns.…”
Section: Grammaticalisationmentioning
confidence: 99%
“…Like the source noun, though, it seems to have retained the sense of ‘male’: with only two exceptions the man pronouns in all four sources of data were uttered by male speakers (the two exceptions were extracted from Anuvahood , uttered by the same female speaker and addressed on each occasion to her boyfriend). Laitinen's () analysis of the development of he, they and those as indeterminate pronouns in Early and Late Modern English found that women strongly disfavoured the use of masculine he as an indeterminate pronoun, presumably, he suggests, because they were avoiding a form that for them indexed masculine gender. Similar gendered patterns are found in studies focussing on the loss of – man in indefinite pronouns.…”
Section: Grammaticalisationmentioning
confidence: 99%
“…First, with regard to the approach whereby democratization is reflected in the discoursepragmatic processes, third-person pronouns are considered to be one of the overt markers of power asymmetry. That is, studies that have looked into democratization proper have observed 6 (27) aspects such as the decline from the early modern period onwards of generic he or the presence of singular they (Laitinen 2008). With regard to more recent changes, various studies have reported substantial shifts in the frequencies of third-person pronouns.…”
Section: Introductionmentioning
confidence: 99%